Kritik Sejarah dan Literasi terhadap Hukum Waris Islam dalam Pandangan David S. Powers - Safrudin Edi Wibowo (Islamica: Jurnal Studi Keislaman, 2010)
Conventionally speaking, the current Muslim law of inheritance is habitually considered as a sufficient and final form of legal formula that reflects the true spirit of Islamic Law ordained by God. The majority of Muslims currently are of belief that the ulama of the first generation have passed down to us the most complete and sophisticated set of law based on their acute interpretation of the Qur?an and the Sunnah. This belief however has now been subjected to a severe criticism by the contemporary critiques especially from the like of David S. Powers. His Studies in Qur?an and Hadith: The Formulation of the Islamic Law of Inheritance that employs the historical and literary criticism approach discovered that there are other sides of Muslim inheritance law. This work challenges the established belief among the traditional Muslims and offers a new legal paradigm whereby a legal ruling must bee seen as reflecting a social and historical dimension. This paper in every respect is a critical review of Powers? book.